Moisture diffusion in the process of extrusion of moistened coarse-broken grains - Skul'skiy, Oleg Ivanivich; Slavnov, Yevgeniy Vladimirovich (Computational Continuum Mechanics, 2008)
The motion of a moistened medium in a single screw extruder is considered. The problem is stated for «reversed motion» (the screw is fixed and the barrel rotates), and the middle longitudinal section of the screw channel is developed onto the plane. The lower boundary of the plane channel moves with the given velocity at an angle to the longitudinal axis. The longitudinal component of the flux determining the output of the extruder is due to the drag force of the channel wall and the counter pressure gradient caused by the die resistance. The circulation motion has no effect on the output, but, owing to intensive mixing, the distribution of moisture over the cross-section of the channel is uniform. The motion of the moistened medium is considered as plane and one-dimensional in velocity and moisture content, but as two-dimensional in pressure. For velocity profile, moisture distribution along the channel and pressure throughout the channel, the analytical expressions have been obtained. The experiment using the laboratory extruder was conducted to measure the moisture content along the channel. It has been found that the experimental and theoretical results agree well.